2023
DOI: 10.3390/nu15081895
|View full text |Cite
|
Sign up to set email alerts
|

Association between Micronutrients and Hyperhomocysteinemia: A Case-Control Study in Northeast China

Abstract: Hyperhomocysteinemia (HHcy) is an independent risk factor for cardiovascular and cerebrovascular diseases where the plasma homocysteine (Hcy) concentration exceeds 15 µmol/L. HHcy is affected by vitamins B12, B6, and folic acid (fol); however, its relationship with other nutrients is not fully understood. We investigated the nutritional and genetic factors associated with HHcy and the possible dose–response relationships or threshold effects in patients in Northeast China. Genetic polymorphisms and micronutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This study had some limitations. First, we could not investigate the effects of several potential factors on Hcy metabolism, such as serum folic acid and vitamin B12 levels and MTHFR C677T polymorphism 65 . Subsequent research should control for these variables to further examine how Hcy is associated with WM microstructural disruption in SZ.…”
Section: Discussionmentioning
confidence: 99%
“…This study had some limitations. First, we could not investigate the effects of several potential factors on Hcy metabolism, such as serum folic acid and vitamin B12 levels and MTHFR C677T polymorphism 65 . Subsequent research should control for these variables to further examine how Hcy is associated with WM microstructural disruption in SZ.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the scope of both studies was limited to postmenopausal women, and thus, the association between dietary calcium intake and serum Hcy levels remains unknown in other adult populations. In a case-control study involving 203 subjects without significant organic disease, a positive correlation emerged between the risk of developing hHcy and plasma zinc concentration and, there was a significant reduction in the risk of hHcy development when the plasma zinc concentration fell below 83.89 μmol/L [ 12 ]. Another study examined blood selenium levels and revealed a significant non-linear relationship with hHcy prevalence, where participants in the upper three blood selenium quartiles had a lower risk of hHcy compared to the lowest quartile of blood selenium concentrations [ 13 ].…”
Section: Introductionmentioning
confidence: 99%